Recent Advances in Mouse Models of Sjögren's Syndrome - Gao, Yunzhen; Chen, Yan; Zhang, Zhongjian; Yu, Xinhua; Zheng, Junfeng (Frontiers in Immunology, 2020)
Sjögren's syndrome (SS) is a complex rheumatoid disease that mainly affects exocrine glands, resulting in xerostomia (dry mouth) and xerophthalmia (dry eye). SS is characterized by autoantibodies, infiltration into exocrine glands, and ectopic expression of MHC II molecules on glandular epithelial cells. In contrast to the well-characterized clinical and immunological features, the aetiology and pathogenesis of SS remain largely unknown. Animal models are powerful research tools for understanding elucidating the pathogenesis of human diseases. To date, many mouse models of SS have been established, including induced models, where disease is induced in mice, and genetic models, where mice spontaneously develop SS-like disease, have been established. These mouse models provide have provided new insight for our understanding ofinto the pathogenesis of SS pathogenesis. In this review, we aim to provide a comprehensive overview of recent advances in the field of experimental SS.